Improved stock unearthing method (Isum) as a tool to determine the value of alternative topographic factors in estimating inter-row soil mobilisation in citrus orchards - Rodrigo-Comino, J.; da Silva, A. M. [UNESP]; Moradi, E.; Terol, E.; Cerdà, A. (Frontiers, 2020)
The Improved Stock Unearthing Method (ISUM) was initially designed to assess soil mobilisation rates in vineyards; however, other grafted crops such as citrus orchards could also be successfully used. The results obtained from ISUM have been used for several goals, but have not yet been applied for computing the LS factor (length and slope) as a part of the Universal Soil Loss Equation (USLE), which could give useful information to improve soil management system plans. This investigation was conducted in an 8-year old clementine field located in Canals (Valencia, Spain) and values of the LS factor were calculated by means of two pre-established algorithms, which allowed us to calculate a Transect Length Index (TLI). Our results demonstrated that the micro-topographical changes can show frequent irregularities For the values of the Transect Length Index (TLI), the mean values were 1.02% for the left side and 1.04% for the right one. The difference among the areas predicted at the moment of furrow construction and the moment of data survey permitted us to estimate a total volume of 56.9 m3 of soil mobilized in 19 years. Taking into account the studied area (360 m2), the volume of mobilised soil, and the bulk density for the local soil (1.3 g cm-3), we estimated a total soil mobilisation of 8.3 mm yr-1 or 10.4 kg m-2 yr-1. We did not observe any evidence or indicator of rill and inter-rill erosion by natural rainfall events, suggesting that the runoff homogenizes the sediment distribution during heavy rains (corroborated by the TLI data) or tillage practices. The data created following the ISUM was suitable to be used to calculate the LS-factor values. The amount of soil mobilised as predicted by USLE was always lower than the ones predicted by ISUM.
Uso del método mejorado del uso del injerto (Isum) como herramienta para determinar el valor de factores topográficos alternativos en la estimación de la movilización del suelo entre hileras para huertos de cítricos
Uso do método melhorado de stock unearthing (Isum) como ferramenta para determinar o valor de fatores topográficos alternativos para estimar a mobilização do solo entrelinhas em pomares de citrinos
Keywords: Agricultural management; Clementine crop; Environmental modelling; Erosive process; LS factor